Acceptance of collective decisions: An experimental study using the mind game and scales of short-run affective state - Ivo Bischoff; Nhat Luong; Konstantinos Madias; Levent Soyalp; Marta Szaban (Philipps-University Marburg, School of Business and Economics, 2024)
We run an experiment on the impact of involvement and outcome favorability on the acceptance of collective decisions. It involves 763 students at the Poznan University of Economics and Management. The collective decision chooses one out of four projects to improve students' study conditions. We measure acceptance by their behavioral and affective response to the decision using the mind game and psychological scales of short-run affective state. We find strong support for outcome favorability for both measures: Subjects whose preferences are not aligned with the collective decision cheat more in the mind game and report a less positive affective state after learning about the outcome of the collective decision than subjects with aligned preferences. We find no differences in the level of cheating across treatments that differ in subjects' involvement. Using the mind game, our paper links the experimental studies on the acceptance of collective decisions to the literature on tax compliance.
Keywords: D72; D82; H26; C90; 330; democratic decision making; experiment; legitimacy; mind game; mood scales; tax compliance; Kant